2018
DOI: 10.3389/fonc.2018.00219
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Immunotherapy and the Immune Response in Follicular Lymphoma

Abstract: Follicular lymphoma (FL) is the most frequent indolent lymphoma in the Western world and is characterized in almost all cases by the t(14;18) translocation that results in overexpression of BCL2, an anti-apoptotic protein. The entity includes a spectrum of subentities that differ from an indolent to a very aggressive growth pattern. As a consequence, treatment can include watch & wait up to intensive chemotherapy including allogeneic stem cell transplantation. The immune cell microenvironment has been recogniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Apart from a combination of CD20‐antibodies and chemotherapeutic agents, other substances aiming at signalling inhibition such as Bruton’s tyrosine kinase inhibitor ibrutinib, the BCL2 inhibitor venetoclax or the selective phosphatidylinositol‐3‐kinase (PI3K) inhibitor idealisib are currently being tested in several studies (Bargetzi et al , ; Cheah & Fowler, ). Further potential new treatment options linked to the emerging field of immunotherapy including PD1/PDL1 checkpoint inhibition and chimaeric antigen receptor therapy (CART) are still in early trial phases or even considered experimental in FL (Stenner & Renner, ). A central finding of our study is the interplay between therapy regimen applied and biomarkers for prognostic prediction exemplified by the fact that several components of the microenvironment only became relevant depending on whether lenalidomide was given.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from a combination of CD20‐antibodies and chemotherapeutic agents, other substances aiming at signalling inhibition such as Bruton’s tyrosine kinase inhibitor ibrutinib, the BCL2 inhibitor venetoclax or the selective phosphatidylinositol‐3‐kinase (PI3K) inhibitor idealisib are currently being tested in several studies (Bargetzi et al , ; Cheah & Fowler, ). Further potential new treatment options linked to the emerging field of immunotherapy including PD1/PDL1 checkpoint inhibition and chimaeric antigen receptor therapy (CART) are still in early trial phases or even considered experimental in FL (Stenner & Renner, ). A central finding of our study is the interplay between therapy regimen applied and biomarkers for prognostic prediction exemplified by the fact that several components of the microenvironment only became relevant depending on whether lenalidomide was given.…”
Section: Discussionmentioning
confidence: 99%
“…We excluded pidilizumab from these studies, since it was recently shown not to bind to PD-1. [10] The remaining 25 mAbs span a wider range of use and include mAbs that may have advanced to various stages of clinical development and others either still in preclinical development or likely serving a control or reagent purpose; some may have historical interest. For example, we included antibodies like mAb01 and mAb14 that were part of the discovery efforts leading to nivolumab and cemiplimab, respectively, and to our knowledge were not advanced to clinical development.…”
Section: Plos Onementioning
confidence: 99%
“…Enhanced infiltration of CD8 + T cells into the GC of LN may impact antibody development and pathogen specific immunity. Of note, recent trials assessing the efficacy of re-programmed autologous CAR T cells for the treatment of follicular lymphoma (FL) demonstrated successful restoration of immune function in patients with relapsed or refractory disease (172); however cytokine release syndrome (CRS) and neurotoxicities were experienced in line with what has been observed in other CAR T cell trials. Additional studies to assess the efficacy of ICI in the context of FL found varying objective response rates with some measured as high as 67% (172).…”
Section: Implications For Immunotherapeutic Interventionsmentioning
confidence: 93%